2015
DOI: 10.3390/toxins7051497
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Components in Fish Venoms

Abstract: Animal venoms are widely recognized excellent resources for the discovery of novel drug leads and physiological tools. Most are comprised of a large number of components, of which the enzymes, small peptides, and proteins are studied for their important bioactivities. However, in spite of there being over 2000 venomous fish species, piscine venoms have been relatively underrepresented in the literature thus far. Most studies have explored whole or partially fractioned venom, revealing broad pharmacology, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 161 publications
(279 reference statements)
1
60
0
3
Order By: Relevance
“…However, our understanding of the factors shaping venom evolution, and our ability to repurpose venom toxins for biotechnological use, is limited by the current focus of research on a small number of prominent groups of venomous animals: the scorpions, spiders, snakes, and cone snails. Studies on neglected taxa (12)(13)(14)(15)(16) are essential to gain a more general understanding of how venom systems evolve and how venom evolution is influenced by factors such as geographical, trophic, and morphological constraints.…”
mentioning
confidence: 99%
“…However, our understanding of the factors shaping venom evolution, and our ability to repurpose venom toxins for biotechnological use, is limited by the current focus of research on a small number of prominent groups of venomous animals: the scorpions, spiders, snakes, and cone snails. Studies on neglected taxa (12)(13)(14)(15)(16) are essential to gain a more general understanding of how venom systems evolve and how venom evolution is influenced by factors such as geographical, trophic, and morphological constraints.…”
mentioning
confidence: 99%
“…SpV was found to perform lethal, hemolytic, cardiovascular, inflammatory, integrin-binding-inhibitory and proteolytic activities [20, 2224, 27, 29]. This spectrum of activities — observed in experimental animals — resembles those of other fish venoms previously described [1, 2]. …”
Section: Biological Activities Of S Plumieri Venom Extract (Spv)mentioning
confidence: 82%
“…Among all the effects caused by fish venoms, cardiovascular activity has been the main subject of research in the field [1, 2]. Clinical reports have shown that the symptoms of S. plumieri envenomation include respiratory distress and tachycardia [11].…”
Section: Biological Activities Of S Plumieri Venom Extract (Spv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fish of toxicological importance are grouped into the venomous category, which present glands specialized in the secretion of venom and a specialized apparatus (spines with canals or canaliculated) for its inoculation 2 . Although accidents caused by these organisms have a low incidence due to their habitat and do not cause mortality in humans, they can cause serious accidents with varying degrees of morbidity for which there is no specific medicine 3 .…”
mentioning
confidence: 99%